2014
DOI: 10.1074/mcp.m113.033803
|View full text |Cite
|
Sign up to set email alerts
|

Functional Proteomic Discovery of Slr0110 as a Central Regulator of Carbohydrate Metabolism in Synechocystis Species PCC6803

Abstract: The unicellular photosynthetic model-organism cyanobacterium Synechocystis sp. PCC6803 can grow photoautotrophically using CO 2 or heterotrophically using glucose as the sole carbon source. Several pathways are involved in carbon metabolism in Synechocystis, and the concerted regulation of these pathways by numerous known and unknown genes is critical for the survival and growth of the organism. Here, we report that a hypothetical protein encoded by the open reading frame slr0110 is necessary for heterotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…2A). The identification of TM-containing proteins from soluble fraction is likely caused by inefficient precipitation of membranous vesicles from the soluble fraction, as previously discussed by us and others (11,28,30,31). If we include only two-or more-TM containing proteins, to exclude proteins with a signal peptide that were otherwise predicted by TMHMM as 1-TM containing, as the true TM-containing proteins, the number of uniquely identified TM-containing proteins can be reduced to 115 and 0 in the membrane and the soluble fractions, respectively, and 133 were from both fractions ( Fig.…”
Section: Fig 1 Rational and Experimental Designmentioning
confidence: 65%
See 3 more Smart Citations
“…2A). The identification of TM-containing proteins from soluble fraction is likely caused by inefficient precipitation of membranous vesicles from the soluble fraction, as previously discussed by us and others (11,28,30,31). If we include only two-or more-TM containing proteins, to exclude proteins with a signal peptide that were otherwise predicted by TMHMM as 1-TM containing, as the true TM-containing proteins, the number of uniquely identified TM-containing proteins can be reduced to 115 and 0 in the membrane and the soluble fractions, respectively, and 133 were from both fractions ( Fig.…”
Section: Fig 1 Rational and Experimental Designmentioning
confidence: 65%
“…Rational and Strategy-It has been repeatedly reported that large scale proteomic analyses for purified membranes identified many non-TM containing proteins that are known to be localized also in soluble fractions such as cytoplasm (11)(12)(13)(27)(28)(29), despite extensive and stringent purification steps being applied to ensure the purity of the isolated membranes. This observation suggested that many non-TM containing proteins have at least two subcellular pools, one pool associated with the membranes through either protein-protein interactions or protein-lipid interactions and the other was in the soluble space.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low intensity blue light pulses can activate glucose metabolism and cell division without initiating photosynthesis [34]. Under heterotrophic conditions, certain membrane proteins of cyanobacteria can upregulate sugar utilization enzymes (e.g., fructose-1,6-bisphosphate aldolase and glucose transporter) and influence glucose uptake rate and dark viability [35]. Thirdly, cyanobacteria are able to close their TCA cycle by 2-oxoglutarate decarboxylase and succinic semialdehyde dehydrogenase [36].…”
Section: Cyanobacterial Photomixotrophic Metabolismmentioning
confidence: 99%